The clinical use and indications for head computed tomography scans in paediatric ambulatory care (short stay ward and medical emergencies) at a children’s hospital over a one-year period, 1st January-31st December 2013 - Machingaidze, Pamela Rudo (Department of Paediatrics and Child Health, 2019)
Background: Computed tomography (CT) imaging is an indispensable tool in the management of acute paediatric illness. It offers quick answers, allowing timely lifesaving decision-making. Clinical evidence is required to maximise its benefits against radiation-exposure risks to patients and cost to the healthcare system. Aims: The study aimed to retrospectively investigate clinical presentation and indications of head CT at a tertiary paediatric hospital. Methods: Records of children presenting with acute illness to the medical emergency unit, excluding trauma, of Red Cross War Memorial Children’s Hospital, Cape Town, over one year (2013) were retrospectively reviewed. Participants were included if they underwent head CT scan within 24 hours of presentation. Clinical data were extracted from records and CT findings reported by a paediatric radiologist. Results: Inclusion criteria were met by 311 patients; 188 (60.5%) were boys. The median age was 39.2 (IQR 12.6-84.0) months. Commonest indications were seizures (n=169;54.3%), reduced level of consciousness (n=140;45.0%), headache (n=74;23.8%) and suspected ventriculoperitoneal shunt (VPS) malfunction (n=61;19.7%). In 217 (69.8%) patients CT showed no adverse findings. In the 94 (30.2%) patients in whom CT abnormalities were detected, the predominant findings were hydrocephalus (n=54;57.4%) and cerebral oedema (n=29;30.9%). Abnormal CT findings were commoner in patients with nausea or vomiting (n=21;9.3%, p=0.05) papilloedema (n=3;1.3%, p=0.015) and long tract signs (n=23;10.2%, p=0.02). Forty-seven patients (15.1%) required surgical intervention after CT of which 40 (85.1%) needed a ventricular drainage procedure. A larger proportion of patients with VPS (25/62;40.3%) required surgical intervention compared to patients without VPS (22/249;8.8%, p <0.001) Conclusion: Most children presenting with acute illness (excluding trauma) and undergoing emergency head CT have normal findings. Patients with ventriculoperitoneal shunts constituted a large proportion of patients requiring intervention after CT. Considerations should be made to use clinical presentation to select patients most likely to benefit from CT.